Language Style Used by The Main Character in Hotel Transylvania 2 Movie - Ni Putu Nia Puspasari; I Made Rajeg; I Nengah Sudipa (FKIP, Universitas Palangka Raya, 2023)
This article aimed at finding out the types of language styles and how it is used by the main character. The object of this article is the main character’s utterances when he speaks with his daughter and his male friends in Hotel Transylvania 2 Movie. The data were collected by the method of documentation and note-taking. The descriptive qualitative and quantitative techniques were applied in accordance with the problems of this article. The theory applied in this article is the theory of language styles introduced by Joos (1967). Based on the article finding, the main character, Dracula, used three types of language styles when talking with his daughter, Mavis, and his male friends, Frankenstein, Wayne, Griffin, and Murray. An intimate style is dominantly used by Dracula when he speaks with Mavis; on the other hand, the casual style is mainly used when he speaks to his male friends. The application of language style by Dracula shows that the relationship affects an individual’s choice of language style. Moreover, a consultative style can be used among insiders to deliver information. In addition, the findings prove that interjection can be the characteristic of the casual or intimate style.